PARAGRAF SEBAGAI DASAR PENYUSUNAN KARYA TULIS YANG EFEKTIF - Jobpri; Ezra Devin Aulaya; Ira Yuniati; Lezita Malianti (STKIP Subang, 2026)
The paragraph is a fundamental element in the composition of written works, as it serves to organize ideas systematically, logically, and clearly. The ability to construct effective paragraphs is a key determinant of writing quality in both academic and non-academic contexts. This article examines the role of the paragraph as a foundation for effective writing by discussing concepts, functions, structures, characteristics, and construction strategies. The study employs a library research method with a qualitative descriptive approach. Data were derived from secondary sources including books, journal articles, proceedings, and relevant scholarly documents and analyzed using content analysis techniques involving data reduction, classification, interpretation, and synthesis. The findings indicate that the paragraph serves as a primary foundation for high-quality writing, as it enables the coherent linking of ideas and facilitates effective information delivery. Paragraphs that adhere to the principles of unity, coherence, and completeness result in discussions that are clearer, more focused, and easier for readers to comprehend. The study also demonstrates that paragraph-writing skills develop through continuous practice supported by the revision process. Consequently, mastering paragraph construction is a fundamental competency that must be cultivated to enhance the quality of written work, particularly in academic writing.